Windfall - Vincenzi, Penny (New York : The Overlook Press, 2009)
Sensible Cassia Fallon has been married to her doctor husband for seven years when her godmother leaves her a huge fortune. For the first time in her life, she is able to do exactly as she likes, and she starts to question her marriage, her past, her present, and her future. But where did her inheritance really come from and why? Too soon the windfall has become a corrupting force, one that Cassia cannot resist.
Originally published in the United Kingdom in 1997.
Keywords: Wealth -- Fiction; Inheritance and succession -- Fiction; Man-woman relationships -- Fiction; Inheritance and succession; Man-woman relationships; Wealth; Domestic fiction; Fiction; Domestic fiction